Une pompe hydraulique romaine en bois en contexte d’incendie à Reims/Durocortorum - Cyril Driard (Gallia)
A wooden water two-cylinder force pump was discovered in 2016 during a rescue archaeological excavation at 45 rue de Thillois in Reims. The discovery of this type of ancient hydraulic device is quite rare. Indeed, it is only the nineteenth specimen to be identified for the Roman Empire and merely the ninth to be discovered in the ancient Roman province of Belgica. During Antiquity, the sector excavated at 45 rue de Thillois was located in the western districts of Durocortorum, 45 m north of the decumanus maximus, 600 m west of the forum and about 400 m from the Vesle river. The remains dating to the Early Empire, unearthed over approximately 800 m2, correspond to a crossroads developing between the 2nd half of the 2nd and the 1st half of the 3rd century.The streets discovered seem to correspond to secondary streets. The largest is oriented northeast/southeast and is 5 m wide. It runs perpendicular to a lane heading towards the decumanus maximus. The well containing the pump was located at the intersection of these two streets. The land located to the north of the most important street seems to have been rather sparsely built upon. Only a small artisanal space dedicated to metalworking (copper alloys) has been identified in this area. Material culture waste also abounds in the sector, though no workshop has been identified. The archaeozoological study suggests the presence of sheep farms and piggeries nearby. South of the street, several city blocks facing south on the decumanus maximus have been identified. The subdivided spaces may correspond to a relatively luxurious residential area, the layers of demolition having notably revealed a remarkable megalography of Dionysos.This district was partially destroyed during a fire after 164-165 AD and before the 2nd half of the 3rd century. The two-cylinder force wooden water pump was used, damaged and discarded in the well during this disaster. The other known Roman pump blocks include both the cylinders and the delivery system. The Reims pump is very different since the cylinders constitute independent parts fixed to a block comprising only the delivery system. Part of the water rise conduit was carved out of this same block, which retained a height of 1.55 m (original height that can be restored using its charred upper end: 1.73 m). The cylinders are approximately 0.14 m wide and 0.57 m high for the right cylinder and 0.58 m for the left cylinder. They had no liners. The pistons were found in situ inside and they are of different design. The one discovered in the right cylinder consists of circular pieces of leather nailed to the end of the wooden sleeve using a single, large iron nail. The left cylinder piston was found degraded. Fragments of leather were found, some revealing a pile of rounded leather disks, beaded around their edges. They were attached quite loosely to a metal piece stapled to the end of the wooden sleeve.The pump was found more than one meter above the bottom of the well, no support was identified and its design did not allow it to be placed at the bottom of the well to operate. The device had a handling system allowing it to be lowered into the shaft. Archaeological observations suggest that this device was not only used to manipulate it during its installation or its removal from the well, but also, a priori, to suspend it during use.In the configuration in which it was found, the cylinder capacity of the Reims pump is evaluated at 1858.24 cm3, its potential flow rate at 22.3 litres per minute, with a pumping rate of 15 revolutions per minute and 66.9 litres per minute, with a higher rate of 45 revolutions per minute. It would, however, appear that the cylinders were modular. Traces of nailing suggest that this pump could have been equipped with taller cylinders, which would have allowed it to reach a higher flow rate, estimated at 41.28 litres per minute, with a pumping rate of 15 revolutions per minute. minute and 123.86 litres per minute, with a rate of 45 revolutions per minute. When last used, the pump required an actual power of 17.95 Ws to operate, with a rate of 15 revolutions per minute and 53.74 Ws, with a rate of 45 revolutions per minute. An adult person could therefore operate it alone at a steady pace. The force required to operate this pump at its last known location is equivalent to 115.46 N, reduced to 76.96 N with the use of a rocker.The Reims pump may correspond to a mobile and modular device temporarily installed within this well, which was not particularly well-suited for such equipment and which was located in the public space. It was last used during a fire. Firefighting is the most frequently cited use of the pump in ancient literature, but heretofore had never been documented by an archaeological discovery.The archaeological context of the discovery of Reims raises the question of possible equipment intended for firefighting. It is likely that a large ancient metropolis as extensive as Reims/Durocorturum was equipped with an organization whose aim was to ensure urban security. The manufacturing techniques and the design method of the Reims pump suggest that it was the work of a body of specialized craftspeople, working in hydraulics. It also suggests that they would have had spare parts or additional modules, or even several other similar devices at their disposal. These observations are reminiscent of the letter to Trajan from Pliny the Younger (Letters, Book X) concerning the fight against fires in urban areas. Cities would have been equipped with the necessary equipment to ensure urban security. The staff was chosen from among the population or certain bodies of specialized craftspeople to accomplish, if necessary, one or more missions.